2019
DOI: 10.18203/2349-3291.ijcp20193706
|View full text |Cite
|
Sign up to set email alerts
|

Study of immunization status of under: five children in relation to various demographic variables of their mothers

Abstract: Background: Immunization remains an important public health intervention. On one side morbidity and mortality caused by vaccine-preventable diseases are still high in developing countries, on the other side immunization coverage is still low. Present study aims to assess immunization status of under-five children in relation to various demographic variables of their mothers.Methods: A total of 530 mothers with children under 5 years attending OPD, immunization clinic or admitted in paediatric ward were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…Regarding caregiver´s education, similar findings have also been reported in studies conducted in Mozambique [ 39 ] and Ghana [ 33 ], where maternal/caregiver education level did not have an impact on the child´s immunization status. The findings from this study are incongruent with the results from other studies conducted in sub-Saharan Africa, where complete immunization was found to be pro-rich [ 24 , 25 , 29 , 40 - 42 ]. This could be because immunizations are provided free of cost in Eswatini.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding caregiver´s education, similar findings have also been reported in studies conducted in Mozambique [ 39 ] and Ghana [ 33 ], where maternal/caregiver education level did not have an impact on the child´s immunization status. The findings from this study are incongruent with the results from other studies conducted in sub-Saharan Africa, where complete immunization was found to be pro-rich [ 24 , 25 , 29 , 40 - 42 ]. This could be because immunizations are provided free of cost in Eswatini.…”
Section: Discussioncontrasting
confidence: 99%
“…The statistical analysis in present study finds that children of mothers more than 30 years of age are more likely to be fully immunised as compared to children to mothers of lesser age. Awasthi et al 3 Differing results vis-à-vis mother's age and full immunisation of children where children of mothers less than 30 years of age were more likely to be fully immunised have been observed in other studies in Indian context [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 98%
“…Even though India's immunisation programme is one of the largest in the world and achieved great success over the years, some significant gaps are still observable in terms of achieving universal immunisation of children. Various forms of struggles, resistance, opposition to immunisation have been documented on account of gender [ [2] , [3] , [4] ], age and education of the mother [ [5] , [6] , [7] , [8] , [9] ], religion [ 8 , [10] , [11] , [12] , 14 , 15 ], region [ 11 , 14 , 16 ], etc. For example, as per National Family Health Survey (NFHS) 4, where Punjab ranks first amongst Indian states with 89% immunisation rate, Nagaland ranks last at 35% immunisation rate.…”
mentioning
confidence: 99%
“…However, mothers who were unskilled labourers did not want to lose their daily wages and found the immunization session timings during their working hours inconvenient resulting in lower 10 immunization coverage of their children. Studies by Engade MB et al , 12 13…”
Section: Discussionmentioning
confidence: 99%